CYTOKINE-PRODUCING FUNCTION OF PERIPHERAL BLOOD CELLS IN COLORECTAL CANCER PATIENTS - A. V. Sosnina; A. I. Autenshlyus; N. V. Velikaya; N. A. Varaksin; M. Yu. Rukhavishnikov; E. S. Mikhailova; D. V. Morozov; S. A. Fursov; N. V. Agarina (Медицинская иммунология)
Аbstract. The aim of present study was to investigate an influence of polyclonal activators upon cytokine-producing function of peripheral blood cells in the patients with colorectal adenocarcinomas. It was revealed that the stimulated production of IL-1β, IL-1ra, IL-2, IL-17, IL-18 and IFNγ by whole blood cells treated with polyclonal activators was significantly decreased in colorectal cancer patients, as compared to healthy individuals. The stimulated IL-1ra and IL-17 production was depressed during the tumor progression, along with increased release of TNFα and IL-8. It was found that the stimulation index of polyclonal activators upon production of IL-17 by whole blood cells (i.e., a cytokine production ratio of stimulated versus resting cells) may be used as a reliable pre-surgery predictor of tumor invasion, the latter being an important histopathological parameter for clinical oncologists. (Med. Immunol., 2011, vol. 13, N 2-3, pp 197-204